Influence of zinc oxide-eugenol temporary cement on bond strength of an all-in-one adhesive system to bovine dentin - Schwartzer, Eduardo (2016)
The objective of this study was to evaluate the influence of temporary zinc oxide-eugenol cements (ZOEs) on the microtensile bond strength (ìTBS) of an all-in-one adhesive system to dentin. Buccal dentin surface of fifteen bovine incisors were exposed and polished with 600-grit SiC paper. Next, three groups were formed: Group 1 (G1), in which the dentin surface was covered with ZOE (TempCem); Group 2 (G2), in which the dentin surface was covered with temporary cement composed of zinc oxide and an aliphatic acid replacing eugenol (TempCem NE); Group 3 (G3) - no temporary cement was used. Each group was individually stored in distilled water at 37° C for 7 days, whereupon temporary cements were mechanically removed. All groups underwent the adhesive protocol with a simplified self-etching adhesive (One-UP Bond F). Four sticks per tooth were obtained, resulting in 20 sticks per group with a cross-sectional area of 0.5 mm2 . The ìTBS test was performed with a crosshead speed of 1mm/min. The failure pattern was analyzed by SEM. The data were submitted to one-way ANOVA, at p<0.05. The mean values were 44.67 MPa for G3, followed by 41.35 MPa for G2 and 39.33 MPa for G1. There was no significant statistical difference between groups. The failure pattern was almost mixed with the adhesive layer and dentin. The eugenol presented in TempCem did not influence the ìTBS test when a simplified selfetching adhesive system was used